Natural Flood Management: Beyond the evidence debate. Issue 4 (21st February 2019) - Wingfield, Thea; Macdonald, Neil; Peters, Kimberley; Spees, Jack; Potter, Karen
Abstract : Globally, flood frequency has increased over the last three decades. Natural Flood Management (NFM) is considered a progressive holistic flood management approach, using "natural" hydrological processes to slow and store water, delivering multiple benefits including water quality, biodiversity and amenity improvements. Although there are existing evaluations of NFM, they remain insufficient for drawing conclusions as to its effectiveness at catchment scales. However, without this evidence base and because of the domination of the natural sciences in the framing and research agenda, catchment‐wide interventions have not been implemented. In acknowledging the importance of understanding and data gaps (and attempts to fill them), this paper argues that there is an opportunity to deliver NFM more widely by capitalising on widespread interest in different land and water management sectors, supported by interdisciplinary policy‐relevant research. This paper illustrates how multi‐stakeholder collaborative partnership is suited to the dynamic complexity of NFM delivery. It is proposed that, through championing NFM delivery at catchment scales and the work of established catchment partnerships in England and Wales, there is the opportunity to more widely deliver NFM as an integrated component of flood risk management. Abstract : This paper illustrates how multi‐stakeholder collaborative partnership is suited to the dynamic complexity of Natural Flood Management (NFM) delivery, arguing that an opportunity exists to deliver NFM more widely by capitalising on widespread interest in different sectors, supported by interdisciplinary policy‐relevant research. It proposes that through championing NFM delivery at catchment scales and working with established catchment partnerships, an opportunity exists to more widely deliver NFM as an integrated component of flood‐risk management.